Analisis Persepsi Komite Pembelajaran dan Praktik Baik Projek Penguatan Profil Pelajar Pancasila pada Kurikulum Merdeka - Arifin Nur Budiono (Journal on Education, 2023)
The independent curriculum is one of the curriculum options laughed at by the government in education units. In the independent curriculum, there is a project program to strengthen the profile of Pancasila (P5) students. This program is an effort to improve character, literacy and numeracy competence in the frame of Pancasila values. The planning and implementation of activities or best practices from the project of strengthening the Pancasila student profile (P5) is influenced by the perceptions of the teachers of the learning committee. This study aims to describe the perceptions of teachers of the learning committee and the good practices of the project of strengthening the profile of Pancasila students. The research method in this study is descriptive qualitative research. The data collection methods used are interviews and observations. The results of this study show that at the beginning of the preparation, there was still a missconception of the learning committee towards the project program to strengthen the profile of Pancasila students. This perception has an impact on planning d.